COMPARATIVE STUDY IN DEVELOPING COFFEE SHOP ENTERPRISES AT MALANG REGENCY AND MATARAM CITY WEST NUSA TENGGARA - Ramdah Radjab; Dewa Made Dirga; Ainul Yakin (International Journal of Social Science, 2021)
Developing Micro, Small and Medium Enterprises (MSME) is a strategic step to increase and strengthen the basis of economic life for most Indonesian people, primarily through providing employment and diminishing poverty rate. Coffee is one of the world's commodities that brought Indonesia to fame. In the coffee industry, a cup of coffee has been named a cup of Java. this research will be dedicated to developing coffee shops in Ampenan Old Town by comparing the strategy for developing coffee shops in Malang Regency, particularly in the DAU area as one of the coffee shops centers in the city. The analysis technique applied in this research is the descriptive qualitative analysis, which systematically, factually, and accurately describes or illustrates a phenomenon related to the studied phenomenon.The strategy of Malang Regency Government by synergizing all policies from entire official institutions and governmental elements is quite neat and sound, including with East Java Province, effected properly on the policies integration from cross-service. In Malang Regency, researchers found creativity and efforts made by MSMEs in dealing with the Pandemic, from regulating operational hours, opening and closing outlets, making packaging products, in collaborating with OJOL (Public Porter), During the Pandemic, there is no right or perfect strategy to overcome it.